Risk management - Sherlock, Jim (Henry Stewart Talks, 2009)
The risk ladder, Country rating, Buyer rating, Open account, When , where and how, Documentary collections, The bill of exchange, Sight and termed drafts, Documentary letters of credit layout, LC operations, Strict compliance, Managing discrepancies, Some rules for getting paid